Serious Games: How do they impact special education needs children - Papanastasiou, George; Drigas, Athanasios; Skianis, Charalampos (Technium Education and Humanities, 2022)
Serious Games appear to benefit children with special needs and provide a multidimensional approach to learning. According to research, Serious Games can help Special Education Needs children stay interested in their study by increasing their motivation, independence, autonomy, and resulting self-esteem. In practically every subject area of the curriculum for preschool and primary education, serious game-based learning has demonstrated its contribution for students with attention, memory, and executive control issues as well as with mental or developmental disabilities.